Development and preliminary validation of the scale of factors which influence decision-making of the elderly to take part in physical exercise programs - Tomažič, Tatjana (Annales kinesiologiae (Koper), 2023)
Regular physical activity and exercise are beneficial for both physical and mental health. However, in the elderly, the level of physical activity they partake in is consist-ently inadequate. Recognizing the need to enhance the participation of the elderly in organized physical exercise and understanding the factors which influence their deci-sion-making becomes pivotal. The purpose of this study was to develop a measurement instrument, specifically a scale, to identify these factors and evaluate its psychometric properties. First, the statements were formulated, which was followed by content as-sessment by a panel of experts. In the process of scale validation, its internal consist-ency, stability, correlations between the variables, and factor structure were also evalu-ated. The scale was tested on a sample of 1777 participants engaged in guided physical exercise at the School of Health Association (društvo Šola zdravja), all aged 60 years or more. Theexploratory factor analysis yielded a four-factor model with 27 state-ments which explained 42.9% of variability. The results indicated weak, but statistically significant correlations between the factors and an acceptable level of internal consist-ency and stability of the entire scale. This scale, developed to establish the factors that influence the decision-making of the elderly to take part in organized physical exercise, represents a valid and reliable measurement instrument, which can be beneficial in the planning and promotion of organized physical exercise programs for the elderly.
Keywords: elderly; gibalna vadba; kvantitativna metodologija; physical exercise; quantitative methodology; social gerontology; Socialna gerontologija; starejši; Telovadba